2010
DOI: 10.1038/nature08878
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic antibody targeting of individual Notch receptors

Abstract: The four receptors of the Notch family are widely expressed transmembrane proteins that function as key conduits through which mammalian cells communicate to regulate cell fate and growth. Ligand binding triggers a conformational change in the receptor negative regulatory region (NRR) that enables ADAM protease cleavage at a juxtamembrane site that otherwise lies buried within the quiescent NRR. Subsequent intramembrane proteolysis catalysed by the gamma-secretase complex liberates the intracellular domain (IC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
604
2
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 651 publications
(638 citation statements)
references
References 41 publications
16
604
2
5
Order By: Relevance
“…41 Other new agents that targeting Notch pathways have also primarily shown effects in inhibiting tumor growth and reducing angiogenesis. 43 Our results demonstrated that knockdown of Notch1 was able to significantly inhibit tumor metastasis from the liver to the lung in a mouse model (Figs. 2a and 2f) and thereby established the potential for targeting Notch signaling as an approach to inhibit tumor metastasis.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…41 Other new agents that targeting Notch pathways have also primarily shown effects in inhibiting tumor growth and reducing angiogenesis. 43 Our results demonstrated that knockdown of Notch1 was able to significantly inhibit tumor metastasis from the liver to the lung in a mouse model (Figs. 2a and 2f) and thereby established the potential for targeting Notch signaling as an approach to inhibit tumor metastasis.…”
Section: Discussionmentioning
confidence: 55%
“…Gamma-secretase inhibitors (GSIs) as inhibitors of key mediators of Notch signaling 41 inhibition of the Notch transcription complex 42 and the development of antibodies targeting individual Notch receptors 43 have shown great potential as new targeted therapeutic agents. GSIs can suppress tumor growth in cell lines and in xenografts in mice 41 through the inhibition of cell proliferation and induction of apoptosis; thus, some GSIs have progressed into Phase I clinical trials.…”
Section: Discussionmentioning
confidence: 99%
“…for targeting the Notch-associated pathobiology. Effectiveness of anti-NRR antibodies in targeting oncogenic Notch signaling in T-acute lymphoblastic leukemia (T-ALL) cell lines has already been reported (32,34). Here, we show effectiveness of the EGF repeats 11 to 12 specific mAbs in selectively affecting ligand-dependent Notch function in breast cancer cell lines.…”
Section: Discussionmentioning
confidence: 77%
“…Individual receptor-specific antibodies against Notch1 and Notch3 NRR domains have been shown to stabilize the receptors in an autoinhibited state and are allosteric in nature (32)(33)(34). However, antibodies specific for the ligand-binding domain of the receptor can serve dual functions of being the potential therapeutic tools while providing insights into the mechanism of ligand binding and subsequent receptor activation.…”
Section: Introductionmentioning
confidence: 99%
“…For manipulation of Notch1 activity in first trimester villous explant cultures, a specific Notch1-blocking antibody (Notch1-IgG1), inhibiting ADAM-mediated cleavage (25), was used (Fig. 2).…”
Section: Notch1 Is Specifically Expressed In Progenitors Of the Extramentioning
confidence: 99%